PENGGUNAAN MODEL PEMBELAJARAN PAKEM (PARTISIPASI, AKTIF, KREATIF, EFEKTIF DAN MENYENANGKAN) UNTUK MENINGKATKAN HASIL BELAJAR SIMBOL LAMBANG NEGARA PANCASILA PADA SISWA KELAS II SD NEGERI 2 JAPARA TAHUN AJARAN 2021/2022 - Haesih (Jurnal Sains Indonesia, 2022)
This Class Action Research is entitled "Use of the PAKEM Learning Model (Participation, Active, Creative, Effective and Fun) to Improve Learning Outcomes of the Pancasila State Emblem Symbol for Class II Students of SD Negeri 2 Japara". The aim is to find out the improvement in learning outcomes of the Pancasila State Emblem Symbol for second grade students of SD Negeri 2 Japara through the use of the PAKEM (Participation, Active, Creative, Effective and Fun) learning model. This research method is classroom action research. The research was carried out in 2 improvement cycles, and each cycle had 2 meetings. The subjects of this study were second grade students of SD Negeri 2 Japara, Kuningan Regency in 2019 in Civics subjects, especially on the material of the Pancasila State Emblem Symbol. The number of students as many as 32 people, consisting of 15 male and 17 female. Data collection techniques in this study were carried out through activities in the form of: (a) action planning; (b) implementation of the action; (c) action observation; and (d) reflection. The results of the evaluation test in the first cycle of the first meeting obtained a class average of 67.5 with a percentage of completeness of 25%. The results of the study can be seen from the average learning outcomes increased from 67.5 at the 1st meeting of Cycle I, to 70 at the 2nd meeting of Cycle I, to 76 at the 1st meeting of Cycle II and to 80 at the 2nd meeting of Cycle II. an increase from 25% at the 1st meeting of Cycle I, to 43.75% at the 2nd meeting of Cycle 1, to 72% at the 1st meeting of Cycle II and to 84% at the 2nd meeting. in each cycle, both meeting 1 and meeting 2. So it can be concluded that the use of the PAKEM learning model (Participation, Active, Creative, Effective and Fun) can improve learning outcomes of the Pancasila State Emblem Symbol for second grade students of SD Negeri 2 Japara.